Students’ supervision and introduction during the initial period in the research laboratory: does it matter? - Marzec, Michal (Improving University Science Teaching and Learning, 2023)
This project reflects on my own experiences and development period covering the last three years of Master student introduction to and supervision at the Department of Biomedical Sciences at UCPH. It consists of Problem statement, questionnaire design covering introduction and the follow up with students, analysis of responses and a discussion of the results and possible adjustments in order to improve the initial period of integration to a new professional environment.